Shari'ah compliance review of prize giving to the premium saving certificate holder: case of Bank Simpanan Nasional / Amira Albhar - Albhar, Amira (2013)
In order to diversify its banking products, Bank Simpanan Nasional (BSN) had introduced Premium Saving Certificate to their customers. Premium Saving Certificate (PSC) offers various prizes to the selected lucky owners of PSC holder through lucky draw voting. This paper aims to analyze several issues regarding to the contract of PSC and the prizes given by the BSN from Shariah perspective. Among the issues that will be discussed includes the element of gambling, riba and violation the condition of Wadiah contract. In this research, data collection will be conducted through various types of references such as books, journal, proceeding papers and others. In order to strengthen the information collected, interviewing method will be performed to obtain first-hand information from the Bank Simpanan Nasional (BSN). This research discovers a non-Shariah compliant feature of premium savings certificates and provides few recommendations to overcome it.